Long-Term Prognostic Value of Stress Cardiovascular Magnetic Resonance in Patients With History of Percutaneous Coronary Intervention. (16th June 2021) - Pezel, Théo; Hovasse, Thomas; Kinnel, Marine; Sanguineti, Francesca; Champagne, Stéphane; Toupin, Solenn; Unterseeh, Thierry; Garot, Philippe; Garot, Jérôme
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Recurrence of cardiovascular events remains a substantial cause of mortality and morbidity among patients with previous coronary revascularization. The aim was to assess the prognostic value of stress cardiovascular magnetic resonance (CMR) parameters in patients with history of percutaneous coronary intervention. Methods: Between 2011 and 2014, consecutive patients with history of percutaneous coronary intervention referred for stress perfusion CMR were followed for the occurrence of major adverse cardiovascular events (MACEs), defined by cardiovascular death or nonfatal myocardial infarction. Patients with prior coronary artery bypass graft were excluded. Univariable and multivariable Cox regressions were performed to determine the prognostic value of each parameter. Results: Of 1762 patients who completed the CMR protocol, 1624 patients (81.7% male, mean age 67.9±10.4 years) completed the follow-up (median [interquartile range], 6.7 [5.6–7.3] years); 244 experienced a MACE (15.0%). Stress CMR was well tolerated. Using Kaplan-Meier analysis, inducible ischemia and late gadolinium enhancement were significantly associated with the occurrence of MACE (hazard ratio, 2.70 [95% CI, 2.11–3.46], P <0.001; and hazard ratio: 1.52 [95% CI, 1.16–1.99], P =0.002; respectively). In multivariable Cox regression, inducible ischemia and late gadolinium enhancement were independent predictors of a higher incidence of MACE (hazard ratio, 2.79 [95% CI, 2.16–3.60]; P <0.001 and hazard ratio, 1.41 [95% CI, 1.04–1.90], P =0.032; respectively). Conclusions: Inducible ischemia and late gadolinium enhancement assessed by stress CMR were independently associated with MACE in patients with history of percutaneous coronary intervention.